Climate resilient agricultural practices for urban growers in Kansas City - Brien Darby; Ami Freeberg (Urban Food Systems Symposium, 2022)
The Kansas City metro is expected to be the fifth most impacted urban environment in the United States with regards to climate change. Research indicates that we will continue to experience increased overall temperatures, increased numbers of heat waves, increased annual precipitation characterized by more extreme precipitation events and longer periods of drought, and increased pest, disease and weed pressure. Furthermore, because of increased heavy downpours throughout the Midwest, Kansas City area farmers report the rains we’ve experienced (such as the 11” of rain that fell over three days in October of 2018) pulverize their soil, resulting in compaction, poor movement of air and water through the soil surface, and crusting. Farmers across our region have begun to experience production, marketing, and management challenges because of changing weather conditions. Yields have become less predictable, pests and diseases have become more prevalent and damaging, sales at outdoor farmers markets becomes more variable in response to extreme temperatures, rain, and wind, and farm business management and planning have become more challenging because of those changes. Cultivate Kansas City recognizes that climate change is a threat to existing and future farm businesses and the local food industry. There is a strong need to educate farmers now to be prepared, to be adaptive, and be resilient with the coming changes to our urban and peri-urban environment. As such, Cultivate Kansas City is committed to providing climate resilient education and resources to urban farmers. In 2020, we launched a project, funded by the Missouri Department of Agriculture, to teach and adapt concepts of farm business resilience to a select cohort of urban farms located in and around Kansas City. In partnership with Laura Lengnick of Cultivating Resilience, two cohorts of farmers (n=13) have participated in workshops, site visits, and one-on-one consultations to identify short-term and long-term goals and strategies to make their farm businesses more resilient. Farmers have also participated in insect pest monitoring and have provided that data to Cultivate Kansas City. Our work with these initial cohorts has allowed us to share some of the lessons learned with a wider farmer audience and we are currently working on two new projects to expand the learning to the refugee farmer population we interact with through the New Roots for Refugees program.
Keywords: climate change; urban agriculture; resiliency; risk management